2020
DOI: 10.1093/ehjci/ehaa946.1153
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT brain glucose metabolism as a marker of different types of depression comorbidity in chronic systolic heart failure patients

Abstract: Background/Introduction Depression comorbidity is an important issue in heart failure (HF) disease. Results from the recent prospective randomized trial MOOD-HF did not provide a rationale for the indiscriminate use of antidepressants in depressed HF patients. Purpose The study investigated whole-brain and regional-brain glucose metabolism in HF patients with 18F-FDG PET/CT and its association with depression comorbidity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…32,33 Previous work has reported associations between depression, reduced systolic function, and hypometabolism in specific brain regions in HF patients, including the amygdala and hippocampus. 23 Unexpectedly, we found that HF patients had similar anxiety and depression scores compared with normal controls, which was likely due to the relatively preserved ejection fraction in our study population (LVEF = 45%), as the severity of HF was associated with depression in patients with HF. 34 In addition, our results showed hypometabolism in cognitive-related brain regions in HF patients, suggesting that cognitive impairment may precede anxiety and depression in the early stage of HF.…”
Section: Cerebral Alterations In Hf Patientssupporting
confidence: 51%
See 1 more Smart Citation
“…32,33 Previous work has reported associations between depression, reduced systolic function, and hypometabolism in specific brain regions in HF patients, including the amygdala and hippocampus. 23 Unexpectedly, we found that HF patients had similar anxiety and depression scores compared with normal controls, which was likely due to the relatively preserved ejection fraction in our study population (LVEF = 45%), as the severity of HF was associated with depression in patients with HF. 34 In addition, our results showed hypometabolism in cognitive-related brain regions in HF patients, suggesting that cognitive impairment may precede anxiety and depression in the early stage of HF.…”
Section: Cerebral Alterations In Hf Patientssupporting
confidence: 51%
“…Previous studies used the region of interest analysis method based on a standard template or manual delineation to explore the hypometabolism brain regions in HF patients. 23 In the present study, we performed a whole-brain voxel-wise analysis by combination of FDG PET and high-resolution T1WI images to comprehensively map brain metabolism. We found that the hypometabolic cluster overlaps with the cluster of structural alterations in patients with HF and covers other cognition-related regions, including the caudate nucleus, precuneus, PCC, calcarine cortex, lingual cortex, and olfactory cortex.…”
Section: Cerebral Alterations In Hf Patientsmentioning
confidence: 99%
“…Theoretically, patients with stable and chronic HF may be more similar to the general population (31). Conversely, in patients recently hospitalized with acute HF, secondary depression due to severe somatic disorders (32) may surpass the effects of a higher BMI and younger age. In this study, COPD and diabetes mellitus were independent predictors of post-discharge depression.…”
Section: Discussionmentioning
confidence: 99%